Postnatal Development of the Murine Notochord Remnants Quantified by High-resolution Contrast-enhanced MicroCT. Issue 1 (December 2017) - Bhalla, Sameer; Lin, Kevin; Tang, Simon
Abstract The notochord gives rise to spinal segments during development, and it becomes embedded within the nucleus pulposus of the intervertebral disc (IVD) during maturation. The disruption of the notochord band has been observed with IVD degeneration. Since the mechanical competence of the IVD relies on its structural constituents, defining the structure of the notochord during aging is critical for investigations relating to IVD function and homeostasis. The assessment and imaging of the notochord has classically relied on histological techniques, which introduces sectioning artifacts during preparation and spatial biases. Magnetic resonance imaging (MRI) does not offer sufficient resolution to discriminate the notochord from the surrounding the nucleus pulposus, especially in murine models. Current X-ray based computed tomography systems provide imaging resolutions down to the single- and sub- micron scales, and when coupled with contrast-enhancing agents, enable the high-resolution three-dimensional imaging of relatively small features. Utilizing phosphomolybdic acid to preferentially bind to collagen cationic domains, we describe the structure of the notochord remnants with aging in the lumbar IVDs of BALB/c mice. These results provide a highly quantitative and sensitive approach to monitoring the IVD during postnatal development.